Women operating the pounding machine - Mumbai Archive Project Team (Jio Institute, 2024)
The pounding machine has a mechanical sieve attached to it, through which the masala is sieved to remove lumps and impurities. The mills are operated by women, who did the work manually in the past using a mortar and pestle.